Baricitinib provides rapid and sustained improvements in absolute EASI and SCORAD outcomes in adults with moderate-to-severe atopic dermatitis - Jacob P. Thyssen; Thomas Bieber; C. Elise Kleyn; Audrey Nosbaum; Susanne Grond; Helmut Petto; Elisabeth Riedl; Andreas Wollenberg (Taylor & Francis Group, 2023)
Background Baricitinib is an oral selective Janus kinase 1/2 inhibitor approved for moderate-to-severe atopic dermatitis (AD) in adults. Objectives To evaluate absolute Eczema Area and Severity Index (EASI) and SCORing of Atopic Dermatitis (SCORAD) outcomes over 16 weeks and to link disease severity categories to quality of life (QoL) improvements. Methods This post-hoc analysis included patients enrolled in Phase3 monotherapy (BREEZE-AD1/AD2) and topical corticosteroid (TCS) combination therapy (BREEZE-AD7) trials and analyzed baricitinib 2 and 4 mg vs. placebo. Categorical outcomes were analyzed using Fisher's exact test. Results Significantly more baricitinib-treated patients reached EASI ≤ 7 and SCORAD < 25 as early as week 1 in monotherapy and week 2 in TCS combination therapy, compared to placebo. Significant response vs. placebo was sustained until week 16 for EASI ≤ 7 (AD1/2 [p-value vs. placebo]: 2 mg = 19.9%, 4 mg = 25.4% [p = 0.001] and AD7: 2 mg = 40.4% [p = 0.087], 4 mg = 48.6% [p = 0.003]) and SCORAD < 25 (AD1/2: 2 mg = 12.2%, 4 mg = 19.4% [p = 0.001] and AD7: 2 mg = 30.3% [p = 0.025], 4 mg = 34.2% [p = 0.004]) severity categories. These effects were accompanied by rapid improvements in QoL. Conclusion Baricitinib-treated patients rapidly achieved recommended absolute EASI and SCORAD treatment outcomes which were sustained until week 16. Improvements in QoL were greater than EASI severity categories reflected, indicating that physician-assessed scores do not necessarily correlate with patients' impression of AD severity.